2000
DOI: 10.1211/0022357001774598
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro Inhibition of Human Erythrocyte Acetylcholinesterase by Salvia lavandulaefolia Essential Oil and Constituent Terpenes

Abstract: Sage (Salvia spp) is reputed in European herbal encyclopaedias to enhance memory, and current memory-enhancing/anti-dementia drugs are based on enhancing cholinergic activity by inhibiting cholinesterase. In this study the effects of Salvia lavandulaefolia Vahl. (Spanish sage) essential oil and some of its constituent terpenes on human erythrocyte acetylcholinesterase were examined in-vitro. The main constituents in the essential oil batch used for analysis of cholinesterase inhibition were camphor (27%), 1,8-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
226
2
8

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(245 citation statements)
references
References 26 publications
9
226
2
8
Order By: Relevance
“…The monoterpene-rich oil of M. myrcioides presented very low effect, with maximum inhibition of 28.9% in the concentration of 600.0 μg.mL -1 . Some monorterpenes have been demonstrated as potent AChE inhibitors, such as the biclyclic α-pinene and (+)-3-carene (Perry et al, 2000;Miyazawa & Yamafuji, 2005). However, the high levels of α-pinene in M. myrcioides volatile oil did not lead to a considerable enzyme inhibition in the present analysis.…”
Section: Resultscontrasting
confidence: 70%
See 1 more Smart Citation
“…The monoterpene-rich oil of M. myrcioides presented very low effect, with maximum inhibition of 28.9% in the concentration of 600.0 μg.mL -1 . Some monorterpenes have been demonstrated as potent AChE inhibitors, such as the biclyclic α-pinene and (+)-3-carene (Perry et al, 2000;Miyazawa & Yamafuji, 2005). However, the high levels of α-pinene in M. myrcioides volatile oil did not lead to a considerable enzyme inhibition in the present analysis.…”
Section: Resultscontrasting
confidence: 70%
“…The volatile oil of Salvia lavandulaefoilia has been shown to inhibit AChE both in vitro and in vivo (Perry et al, 2000;. Additionally, some isolated bicyclic monoterpenes, especially α-pinene and (+)-3-carene, also presented a strong inhibition of this enzyme (Miyazawa & Yamafuji, 2005), as well as some sesquiterpenes, such as α-and β-ionone and nootkatone (Miyazawa et al, 1998a;.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, below will be presented the biological activities, described in scientific literature, to the essential oils found in the plants used for produce the "tira-capeta" cigarette, where some correlations tentatively were carried out between these activities and the therapeutical uses reported by the Quilombolas. Perry et al (2000) verified that α-pinene, 1,8-cineole and camphor have uncompetitive and reversible acetylcholinesterase inhibitory activity. It is known that compounds with anticholinesterase properties improved memory and attention in people (Scholey et al, 2008).…”
Section: Biological Activity Of Essential Oils Found In This Analysismentioning
confidence: 85%
“…In fact, the essential oils of the samples of the two varieties of C. sempervirens used in this study were analyzed by GC-MS in our previously [9] and a-pinene was the main components as follows; CSH-Cone: 66.75%; CSH-Leaf: 56.91%; CSP-Cone: 52.52%; CSP-Leaf: 37.91%. In many previous studies [32][33][34], a-pinene has been shown to inhibit strong cholinesterase inhibitory activity and moderate inhibitory activity of the Cupressus extracts could be related to their a-pinene content, although they are not supposed to contain a-pinene as much as the essential oil per se. Probably, apolar extracts have more possibility to contain this component, where the acetone and dichloromethane extracts were active in our assays.…”
Section: Discussionmentioning
confidence: 99%